Factores biosociales y actitud de la madre del recién nacido hospitalizado en el inicio de la lactancia materna. Hospital Victor Lazarte Echegaray, Trujillo - Montoya Guevara, Reyna Jacqueline (2015)
This descriptive correlational and cross-sectional study was conducted on 100 mothers of newborns hospitalized in the hospital of Trujillo Victor Lazarte Echegaray in order to determine the relationship between maternal factors: age, occupation, education level and number of children above and maternal attitude at the start of breastfeeding the newborn hospitalized at the Intermediate unit and intensive care. It came to the following conclusions: 34 percent of mothers are between 30-34 years, 76 percent have home as an occupation, 49 percent reached the degree of secondary education, and 59 percent have had previous children. The predominant maternal attitude toward breastfeeding in newborn hospitalized unfavorable 82 percent, only 18 percent are in fairly favorable attitude. No case (0 percent) was found in favorably. The family support dimension stands with the highest percentage in fairly favorable attitude. There is significant statistical relationship between educational attainment and the attitude of the mother of the newborn hospitalized at the beginning of breastfeeding (p = 0.029). There is no statistically significant relationship between age, occupation and previous children and the attitude of the mother.